2014
DOI: 10.1002/jaba.116
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and accumulated reinforcement arrangements: Evaluations of efficacy and preference

Abstract: We assessed the efficacy of, and preference for, accumulated access to reinforcers, which allows uninterrupted engagement with the reinforcers but imposes an inherent delay required to first complete the task. Experiment 1 compared rates of task completion in 4 individuals who had been diagnosed with intellectual disabilities when reinforcement was distributed (i.e., 30-s access to the reinforcer delivered immediately after each response) and accumulated (i.e., 5-min access to the reinforcer after completion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
102
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(124 citation statements)
references
References 54 publications
(44 reference statements)
7
102
4
4
Order By: Relevance
“…For example, data obtained across methods suggest that qualitative differences inherent in magnitude or continuity can influence value. This extends previous literature exploring factors that can impact reinforcer value (DeLeon et al, 2014;Steinhilber & Johnson, 2007). Future research should explore comparisons of the Bnatural value^of a stimulus versus the Boptimal value.^In other words, does the difference in magnitude of a stimulus in the context of intervention sessions and how the individual consumes the stimulus in the natural environment matter?…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…For example, data obtained across methods suggest that qualitative differences inherent in magnitude or continuity can influence value. This extends previous literature exploring factors that can impact reinforcer value (DeLeon et al, 2014;Steinhilber & Johnson, 2007). Future research should explore comparisons of the Bnatural value^of a stimulus versus the Boptimal value.^In other words, does the difference in magnitude of a stimulus in the context of intervention sessions and how the individual consumes the stimulus in the natural environment matter?…”
Section: Resultssupporting
confidence: 65%
“…More recently, DeLeon et al (2014) found that participants demonstrated a preference for accumulated reinforcers, rather than equally distributed amounts. From a practical standpoint, this raises a potential issue regarding the manner in which stimuli are presented during a preference assessment.…”
mentioning
confidence: 99%
“…Several studies have shown that, under certain conditions, participants prefer to complete a larger set of responses followed by longer duration of access to a reinforcer instead of completing several smaller sets of responses followed by brief reinforcer access that result in the same overall amount of work and reinforcement (Bukala, Hu, Lee, Ward-Horner, & Fienup, 2015;DeLeon et al, 2014;Fienup, Ahlers, & Pace, 2011;Ward-Horner, Pittenger, Pace, & Fienup, 2014). For instance, Fienup et al (2011) provided a participant a choice to complete either 120 math problems consecutively followed by 18 min of reinforcer access (continuous arrangement) or six sets of 20 math problems with each set followed by 3 min of reinforcer access (discontinuous arrangement).…”
mentioning
confidence: 99%
“…There have been several replications of Fienup et al (2011) that have largely focused on variables influencing preference and performance for response-reinforcer arrangements with older participants who generally preferred a continuous arrangement (e.g., DeLeon et al, 2014;Kocher, Howard, & Fienup, 2015;Ward-Horner et al, 2014). For instance, DeLeon et al (2014) investigated the effects of the type of reinforcer on preference by providing access to edible and activity reinforcers.…”
mentioning
confidence: 99%
See 1 more Smart Citation